A Study on Student's Perception Towards The Quality of Services Provided by The Library, University Malaysia Pahang (UMP) - Suziyana, Mat Dahan; Mohd Yusof, Taib; Nurhaizan, Mohd Zainudin; Fadzida, Ismail; Ahmad Nazif, Noor Kamar (2013)

(untitled)
The intense competition among academic institutions has forced the academic libraries to deliver the best services in aiding the student's advancement in academic discipline.